A Bond-Weakening Borinate Catalyst that Improves the Scope of the Photoredox α-C–H Alkylation of Alcohols - Sakai, Kentaro; Oisaki, Kounosuke; Kanai, Motomu (Synthesis, 2020)
The development of catalyst-controlled, site-selective C(sp3)–H functionalization reactions is currently a major challenge in organic synthesis. In this paper, a novel bond-weakening catalyst that recognizes the hydroxy group of alcohols through formation of a borate is described. An electron-deficient borinic acid–ethanolamine complex enhances the chemical yield of the α-C–H alkylation of alcohols when used in conjunction with a photoredox catalyst and a hydrogen atom transfer catalyst under irradiation with visible light. This ternary hybrid catalyst system can, for example, be applied to functional-group-enriched peptides.
Keywords: photoredox catalyst; hydrogen atom transfer catalyst; boron; bond-weakening; C–H functionalization